Factors influencing the uptake of contraceptives among youth in Imenti South subcounty, Meru county, Kenya - Manene Kiende Agnes (Meru Agnes Kiende Manene, 2023)
Contraceptive methods have been in use since 1960s although underutilized in most countries. Pregnancies which are too many, too early and too frequent result in maternal child morbidity and mortality. Unintended pregnancy poses a major risk to the reproductive health of adolescence and young adults in developing countries noted as a result of the decreasing age of men arch and onset of sexual activity. This has a serious implication on economy and future human capital potential. Delivery of effective contraceptive services has a direct impact on maternal child wellbeing. The aim of the study was to determine factors influencing uptake of contraceptives among youth in Imenti south sub-county Meru County. The specific objectives of the study were to assess the social factors, determine the economic, individual factors and identify health service factors influencing the uptake of contraceptives the youth ages 18-24 years in Imenti South Sub-County Meru County. Collecting data about the uptake of contraceptives by youth is of importance in the prevention of teenage pregnancy, termination of pregnancy and transmission of sexually transmitted infections. The study will provide data information to assist policy makers in developing appropriate evidence-based strategies to promote knowledge on utilization of contraceptives use and help develop innovative and cost effective strategies for improving basic information and utilization among the youth. The findings of the study will be utilized by the Ministry of Health through community health work force to ensure the youth have the right information discussions on utilization of contraceptives. Questionnaires, in-depth interview guide and focused group were used for data collection. Out of the 1230 households in the sub county a sample of 146 respondents were systematically selected among the households by use of systematic random sampling method, where every 8th house hold was included. The results of the study showed that mean age group was 22.4. Information based on the social factors that influence uptake of contraceptives; there was significant association between intended number of children and uptake of contraceptives. Economic factors - Source of income significantly influenced uptake of contraceptives where those who had their own source of income were utilizing compared to others who were on their other sources. Individual factors - knowledge regarding what contraceptives were used for significantly influenced the uptake of contraceptives. For the facility based factors there was significant association between waiting time and utilization of contraceptives and Information on side effects of contraceptives was significantly related to uptake. Emanating from the study the following recommendations are made in older to improve on uptake of contraceptives: administrators should strengthen capacities to provide essential reproductive health services among the youth, incorporation of reproductive health information in curriculums and demonstrated need for better client counseling. The health administrators should strengthen capacities to provide essential reproductive health services among the youth in order to reduce the level of misinformation of contraceptives. There is need to Provide sex education and accurate knowledge on family planning and birth control as well as suggesting effective contraceptive methods to this particular age group. The medical officer in charge of Local health sector should collaborate with youth programs in the community through community leaders and ensure the youth have access to information on reproductive health. The County Director of education and policy makers should ensure incorporation of reproductive health information in curriculum to improve knowledge on family planning issues.
Factors influencing the uptake of contraceptives among youth in Imenti South subcounty, Meru county, Kenya
Keywords: uptake of contraceptives